The global coffee paradox and coffee marketing in Zimbabwe; 1980-2000 - Taringana, Takesure (Africanus: Journal of Development Studies, 2018)
This article examines coffee marketing in Zimbabwe amidst debates on the contribution of agricultural commodities to sustainable economic development in Africa. It uses the concept of linkages and declining terms-of-trade to reconnoitre these debates. The article argues that between 1980 and 2015, coffee production, and in particular marketing, faced a myriad of internal and external challenges, which limited its overall contribution to the economy. Among these constraints was the lack of a significant domestic market, which tied the sector to external markets. The externality of the coffee industry weakened the linkages between the sector and the rest of the local economy, thereby turning the sector into an enclave of external economies. This exposed the industry to risks on the international market— including price volatility. The setup perpetuated the unfair global division of labour, where Zimbabwe suffered declining terms-of-trade as an exporter of raw coffee and an importer of manufactured products. This article, therefore, contends that the externality of the coffee industry in Zimbabwe plunged the country into an exploitative dependency relationship with consuming countries. Failure to export processed coffee was mainly a function of the restrictive tariff policies in the consuming countries.